Studies in South-Occidental Amazon: contribution to the knowledge of Brazilian Chironomidae (Insecta: Diptera) - doi: 10.4025/actascibiolsci.v34i2.9195 - Vieira, Lisandro Juno Soares; Rosin, Gisele Cristina; Takeda, Alice Michyio; Lopes, Maria Rosélia Marques; Sousa, Daniel Silva de (Acta Scientiarum. Biological Sciences, 2011)
Chironomidae (Diptera) are a diverse and large group of small flies, whose larvae inhabit nearly every possible niche in most freshwater aquatic ecosystems. The Acre river is an important affluent of the Purus river. Our objective was to contribute to the knowledge of Chironomidae in this region by making the first survey of Chironomidae composition in the Acre river (Amazon Basin), and relate its distribution to physical and chemical variables. Samples were collected at three sites using a modified Petersen grab. A grain size analysis showed heterogeneity between sampling sites. Eighteen morphospecies of Chironomidae larvae were recorded. In site 2, there was higher density of Chironomidae. Higher richness was observed in site 1, and the composition of this site was similar to site 3. The present study showed that the Chironomidae community was influenced by urban area. Chironomidae can be considered an important component of the fauna of this river and a potential instrument in future studies of ecology in the region.